Analysis of the Development of Information and Communication Technology in Supporting Office Administration in Serang City - Banten - Hillyah Maulidah; Eli Apud Saepudin; Rofika; Reviana Utari; Resma Cahya; Siti Salasatu Sa'diyah (Pt. Anagata Sembagi Education, 2024)
Technological developments have entered various fields, both formally and informally. One technology that is developing very quickly at the moment is the communication system. With the development of the internet, communication can be done from anywhere and at any time. Basically, office administration is an activity that is closely related to the administration system in an office, various applications according to needs and services can be implemented so that implementation is more effective and efficient. This activity is very beneficial and useful for government and office employees, especially to speed up service. Therefore, it is important for us to make optimal use of ICT to build a better future. This article's research method uses a qualitative descriptive method where all problems and solutions are related to the theme and are taken from various sources. This approach aims to describe and understand in depth about the development of ICT and its influence on office administration in Serang City. The results of the study are expected to provide a comprehensive picture of the development of ICT and its influence on office administration in Serang City.